Urgensi Ekonomi Islam dalam Menjawab Tantangan Sistem Kapitalisme Modern - Renaldi, Rizal (ECONOMETRICS:Journal of Sustainable Economics and Management, 2025)
This study analyzes the urgency of Islamic economics in responding to the structural and moral challenges of modern capitalism. Although capitalism has contributed significantly to economic growth and technological advancement, it has also generated systemic problems such as income inequality, wealth concentration, financial instability, and ethical degradation in market practices. Using a qualitative-descriptive approach with library research methods, this study examines contemporary academic literature (2019–2024) to compare the fundamental paradigms of capitalism and Islamic economics. The findings indicate that Islamic economics offers a comprehensive alternative framework grounded in justice (‘adl), public welfare (maṣlaḥah), and moral responsibility (akhlaq). By prohibiting riba, gharar, and maysir, and promoting profit-and-loss sharing mechanisms such as mudarabah and musharakah, Islamic economics integrates financial activities with real-sector productivity and equitable risk distribution. Furthermore, redistributive instruments such as zakat, infaq, and waqf strengthen social solidarity and economic inclusiveness. Despite its strong ethical foundation and growing global relevance, Islamic economics faces challenges including limited financial literacy, regulatory disparities, and the dominance of conventional capitalist systems. The study concludes that Islamic economics is not merely a technical alternative but a moral-economic paradigm capable of fostering a more just, inclusive, and sustainable global economic order